Oil and Gas Marketing Strategies in the Global Energy Market - Jumaah, Abbas Ali (Goodwood Akuntansi dan Auditing Reviu, 2025)
Purpose: This study aimed to determine the prevalence and determinants of routine immunization default among mothers of children aged 0–59 months in Ido Local Government Area (LGA), Oyo State, Nigeria, and to evaluate the effectiveness of implemented catch-up strategies. Methodology/approach: A descriptive cross-sectional study was A cross-sectional study of 420 mothers used questionnaires and SPSS 26 for analysis, with logistic regression identifying predictors of default. Key informant interviews with healthcare providers assessed catch-up strategies and barriers. Results/findings: The study revealed an immunization default rate of 34.8%. The main reasons cited for defaulting included lack of awareness of return dates (41.2%), long distances to health facilities (26.5%), and vaccine stock-outs (19.3%). Significant predictors were maternal education level (p=0.002), place of delivery (p=0.015), and knowledge of immunization schedules (p<0.001). Catch-up strategies such as house-to-house visits, SMS reminders, and mobilization by religious and traditional leaders were moderately effective but insufficient in hard-to-reach areas. Conclusions: Routine immunization defaulting persists as a significant public health challenge in Ido LGA. Socioeconomic, educational, and systemic barriers hinder full coverage, necessitating more robust interventions Limitations: The cross-sectional design restricts causal inference, and self-reported data may introduce recall bias. Contribution: The study provides empirical evidence to strengthen catch-up strategies and guide policy toward equitable immunization coverage.